CAPN3 c.1746-20C>G variant is hypomorphic for LGMD R1 calpain 3-related - Mroczek, Magdalena; Inashkina, Inna; Stavusis, Janis; Zayakin, Pawel; Khrunin, Andrey; Micule, Ieva; Kenina, Victorija; Zdanovica, Anna; Zídková, Jana; Fajkusová, Lenka; Limborska, Svetlana; van der Kooi, Anneke J; et al. (Human mutation, 2022)
The investigated intronic CAPN3 variant NM_000070.3:c.1746-20C>G occurs in the Central and Eastern Europe with a frequency of >1% and there are conflicting interpretations on its pathogenicity. We collected data on 14 patients carrying the CAPN3 c.1746-20C>G variant in trans position with another CAPN3 pathogenic/likely pathogenic variant. The patients compound heterozygous for the CAPN3 c.1746-20C>G variant presented a phenotype consistent with calpainopathy of mild/medium severity. This variant is most frequent in the North/West regions of Russia and may originate from that area. Molecular studies revealed that different splicing isoforms are produced in the muscle. We hypothesize that c.1746-20C>G is a hypomorphic variant with a reduction of RNA and protein expression and only individuals having a higher ratio of abnormal isoforms are affected. Reclassification of the CAPN3 variant c.1746-20C>G from variant with a conflicting interpretation of pathogenicity to hypomorphic variant explains many unidentified cases of limb girdle muscular dystrophy R1 calpain 3-related in Eastern and Central Europe.
Keywords: svalové proteiny; CAPN3; Mutation; mutace; hypomorphic variant; LGMD; Muscular Dystrophies, Limb-Girdle; Muscle Proteins; calpainopathy; RNA Splicing; Calpain; LGMD R1 calpain 3-related; pletencové svalové dystrofie; Humans; lidé; kalpain; sestřih RNA